Synthesis and characterization of a fluorescent magnetic molecularly imprinted polymer for enhanced adsorption and selective extraction of pesticides from agricultural waters - Ali, Zeeshan; Raza, Nadeem; Hayat, Muhammad; Khezami, Lotfi; Khairy, Mohamed; Almuqri, Eman Abdullah; Basher, Nosiba S.; Parveen, Humaira; Chaudhary, Anis Ahmad (Frontiers in Nanotechnology, 2024)
IntroductionA novel fluorescent magnetic molecularly imprinted polymer (FMMIP) was developed for the effective extraction of malathion (MLT) and chlorpyrifos (CPS) from agricultural water sources.MethodsThe FMMIP was confirmed to have a stable polymer structure with significant thermal resilience through comprehensive characterization using techniques such as TEM and TGA. The magnetic properties of the FMMIP facilitated easy separation by external magnetic fields, with a notable magnetization of 0.006 emu/g. Kinetic and isotherm studies revealed that adsorption of MLT and CPS onto the FMMIP conformed best to the pseudo-first-order model and Freundlich isotherm, suggesting a predominance of physisorption mechanisms and heterogeneous binding sites.Results and DiscussionThe FMMIP demonstrated exceptional adsorption capacities, achieving a maximum of 93 mg/g for MLT and 69 mg/g for CPS. Regeneration trials indicated that the FMMIP maintains its high adsorptive performance over multiple cycles, highlighting its potential for sustainable use. Statistical validation confirmed the method’s reliability, with RSD values for MLT and CPS at 6.5% and 7.3%, respectively, and LODs determined to be 1.26 mg/L for MLT and 1.22 mg/L for CPS. The strong R2 values of 0.992 for MLT and 0.998 for CPS from the adsorption studies substantiate the method’s effectiveness. This study demonstrates that the synthesized FMMIP is a promising material for removing MLT and CPS, supporting its application in environmental clean-up initiatives to protect and preserve ecosystems.